Psychological effects of tablecloth color on diners under different brightness - Ono, Makiko; Tomita, Keiko; Aiba, Terumi; Ohtani, Kimiko (Journal for the Integrated Study of Dietary Habits, 2007)
The effective use of the tablecloth color to produce a comfortable dining space was examined under different brightnesses. The tablecloth color was shown to produce not only a comfortable, but suitable atmosphere that changes one's emotion depending on the TPO. The stronger the brightness, the more characteristic tablecloth color was strengthened, especially yellow. In a dark room with dim light, the characteristics of the tablecloth color diminished. In order to promote one's appetite and conversation, yellow, beige and white tablecloths were effective under a high brightness. In order to produce a healing space, a beige tablecloth under 400-600 lux was suggested to be most recommended. The effective use of the tablecloth color and illuminance were shown to be useful to change a diner's emotion and to improve the diner's QOL.